Literasi Keuangan, Perencanaan Keuangan & Bussiness Sustainability pada Pengelolaan Keuangan - Ratih Eka Sakti; Susyanto Tunut; Endar Pradesa (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of financial literacy, financial planning and business sustainability on the financial management of young entrepreneurs in North Musi Rawas Regency. Quantitative data type research methods are processed with SPSS For Windows as a tool for calculating data. Sampling method using simple random sampling method. The number of research samples was 31 respondents from young entrepreneurs in North Musi Rawas Regency. The data analysis technique uses multiple linear regression using SPSS. The results of the study show that financial literacy has a positive effect on financial management as evidenced by the results of the t test which show a significant value of 0.21 <0.05, Financial planning is proven by the results of the t test of 0.25 <0.05 and the sustanibility of financial management is proven with 0.23 <0.05. In conclusion, the better the level of financial literacy, financial planning, and business sustainability, the better the level of financial management of young entrepreneurs. Keywords: Financial Literacy, Financial Planning, Business Sustainability